1994
DOI: 10.1046/j.1471-4159.1994.63041377.x
|View full text |Cite
|
Sign up to set email alerts
|

Localized 13C NMR Spectroscopy in the Human Brain of Amino Acid Labeling from d‐[1‐13C]Glucose

Abstract: Cerebral metabolism of D[1-"C]glucose was studied with localized '3C NMR spectroscopy during in-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
157
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 236 publications
(167 citation statements)
references
References 30 publications
8
157
0
Order By: Relevance
“…A number of investigations have reported increased levels of Glx, the combined signal arising primarily from glutamate and glutamine, in the frontal lobes, basal ganglia, left dorsolateral prefrontal cortex (DLPFC), and global gray matter of drug-free bipolar subjects 30,60,61 (Table 4). Although the Glx peak is difficult to separate into glutamate and glutamine at the relatively low magnetic field strengths used in human studies, 62 an increased Glx signal is likely to imply alterations in the overall glutamate/glutamine cycle.…”
Section: Elevated Lactate In Bipolar Disordermentioning
confidence: 99%
“…A number of investigations have reported increased levels of Glx, the combined signal arising primarily from glutamate and glutamine, in the frontal lobes, basal ganglia, left dorsolateral prefrontal cortex (DLPFC), and global gray matter of drug-free bipolar subjects 30,60,61 (Table 4). Although the Glx peak is difficult to separate into glutamate and glutamine at the relatively low magnetic field strengths used in human studies, 62 an increased Glx signal is likely to imply alterations in the overall glutamate/glutamine cycle.…”
Section: Elevated Lactate In Bipolar Disordermentioning
confidence: 99%
“…[17][18][19]28,33 In 1994 it was first demonstrated that in vivo 13 C NMR may be used to measure the rate of glutamine labeling from 1-13 C glucose in human occipital/parietal cortex. 18,27 However the rate of the glutamate/glutamine cycle was not uniquely determined from these first experiments due to the inability to distinguish the glutamate/glutamine cycle from other sources of glutamine labeling in the glia. The studies in rats by Sibson and coworkers 29,30 allowed a constraint to be placed on the maximum flow of label from glial pyruvate dehydrogenase into glutamine as the rate of anaplerosis.…”
Section: Mrs Studies Of Neuronal Glial Gluta-mate Traffickingmentioning
confidence: 99%
“…It has been shown that the strong lipid signal in natural abundance 13 C NMR spectra of the human head is from extra-cerebral tissue and normal human brain does not contain detectable triacyl-glycerol resonances (Gruetter et al, 1994b(Gruetter et al, , 1996. Application of the localization method to the human head routinely suppressed the triacyl-glycerol resonances at 30.5 ppm more than 100-fold (n = 10 subjects without glucose infusion, Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The excellent reproducibility was in part due to a conservative time resolution of 25 min, however, the current sensitivity certainly would permit a temporal resolution of 10-15 min. Conversely, the sensitivity of the current experiment should allow reduction of the volume size from 210 to 140 ml, which is a spatial resolution that has been used in different, unrelated studies (Gruetter et al, 1994b;Shen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%